تأثير الإشباع المغناطيسي للقلوب على بارامترات المولدات التواقتية والحالات العابرة فيها - ابراهيم طارق; شعبان فيصل (Latakia University Journal -Engineering Sciences Series, 2019)
تتعلق الحالات العابرة في نظم القدرة الكهربائية ببارامترات الآلات الكهربائية، وبالتالي بكثافة استخدام المواد الفعالة فيها وبإشباع دارة المغنطة. يتناول البحث طريقة حساب اشباع الفولاذ على مسارات التدفق المغناطيسي الأساسي، وعلى مسارات تدفقات التسرب للحلقات كما يتطرق إلى تأثير الاشباع على البارامترات الأساسية لنظام العمل المستقر، وكذلك تأثيره على كل من حد الاستقرار الديناميكي وتخميد اهتزازات الآلة التواقتية . The transient condition in the power systems are related to parameters of electrical machines, and consequently to density of using of active materials in it, and to saturation of magnetic circuit. So the research tackles a method to calculate saturation of steel on the path of basic magnetic flow, and on the paths leakage flows to lings. In addition, it searches the effect of saturation on the basic parameters of steady state system, and on the limit of dynamic stability, and damping vibration of synchronous machine.